Overview of Dental Caries and Treatment Needs in Early Childhood - Yudha Rahina; I Gusti Agung Ayu Chandra Iswari Dewi; I Nyoman Panji Triadnya Palgunadi; Ni Putu Idaryati; I Wayan Agus Wirya Pratama; I Gusti Ayu Ratih Pramesti; Gusti Ayu Yohanna Lily (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction: The prevalence of dental caries in children remains high in Indonesia. Primary teeth are particularly vulnerable to caries, yet parental awareness of children's oral health is often insufficient. As a result, children with caries often do not receive proper treatment. It is unfortunate when caries occur at an early age. This study aims to describe the occurrence of dental caries and the need for dental treatment in early childhood. Material and Methods: This study utilized a descriptive-analytic method with a cross-sectional approach, which involved 52 children, aged 3 to 5 years. Dental caries were assessed using the def-t index, while treatment needs were evaluated with the Required Treatment Index (RTI). The data collected were analyzed descriptively and further examined using the Mann-Whitney and Spearman's rank correlation test. Results and Discussions: The prevalence of dental caries in children was 57.69%, with an average def-t score of 2.62. Caries were most commonly found in the upper jaw, particularly affecting the primary first incisors, followed by the primary molars. The treatment needs index (RTI) was 99.26%, indicating that most carious teeth were left untreated, requiring dental treatment. There was no significant caries difference between boys and girls (p > 0.05). However, a significant correlation was found between age and caries frequency (p < 0.05). Conclusion: The average caries rate in primary teeth falls within the low category. However, nearly all affected teeth require treatment. Among children aged 3 to 5 years, caries prevalence tends to increase with age, and no difference between boys and girls.